Learning lessons from adverse drug reactions in children - Sammons, Helen; Choonara, Imti (MDPI, 2016)
Drug toxicity is, unfortunately, a significant problem in children both in the hospital and in the community. Drug toxicity in children is different to that seen in adults. At least one in 500 children will experience an adverse drug reaction each year. For children in hospital, the risk is far greater (one in ten). Additionally, different and sometimes unique adverse drug reactions are seen in the paediatric age groups. Some of the major cases of drug toxicity historically have occurred in neonates. It is important that we understand the mechanism of action of adverse drug reactions. Greater understanding alongside rational prescribing should hopefully reduce drug toxicity in children in the future.